Who Chooses Annuities? An Experimental Investigation of the Role of Gender, Framing, and Defaults - Agnew, Julie R; Anderson, Lisa R; Gerlach, Jeffrey R; Szykman, Lisa R (American Economic Review, 2008)
Who Chooses Annuities? An Experimental Investigation of the Role of Gender, Framing, and Defaults by Julie R. Agnew, Lisa R. Anderson, Jeffrey R. Gerlach and Lisa R. Szykman. Published in volume 98, issue 2, pages 418-22 of American Economic Review, May 2008